2019
DOI: 10.1186/s12889-019-6730-4
|View full text |Cite
|
Sign up to set email alerts
|

Income and education predict elevated depressive symptoms in the general population: results from the Gutenberg health study

Abstract: Background Socioeconomic status (SES) has a strong association with depression or physical and mental health in general. However, as SES is a multifaceted construct these associations are not easy to explain. Further, there are several indicators and many studies only investigating two or less indicators at the same time. Therefore, this study aims to analyze the cross-sectional and longitudinal association of three defined SES dimensions (education, occupational position and household net-income)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 34 publications
3
27
1
1
Order By: Relevance
“…Education was a significant factor for explaining severe depression in BC survivors. The protective role of education against the development of depression has been shown before 31 . In healthy adults, lower education is also associated with a higher cancer fatalism and less information seeking 32 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Education was a significant factor for explaining severe depression in BC survivors. The protective role of education against the development of depression has been shown before 31 . In healthy adults, lower education is also associated with a higher cancer fatalism and less information seeking 32 .…”
Section: Discussionmentioning
confidence: 96%
“…The protective role of education against the development of depression has been shown before. 31 In healthy adults, lower education is also associated with a higher cancer fatalism and less information seeking. 32 However, in our study, education was not associated with mild depression in BC survivors and neither mild nor severe depression in controls.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the average scores of SAS and SDS scales decreased with increasing educational levels among SCA patients. Previous studies have reported a momentous association between lower education and severe depression [23]. In contrast, patients with college education can better regulate themselves, communicate better with doctors, actively collect the latest research advances of SCA, and learn more about the current situation about COVID-19 from the media, which can reduce anxiety and depression to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…A U-shaped relationship between weekly working hours and mental ill health makes sense. On one hand, prolonged workweeks may increase family incomes, which are known to be inversely associated with the risk of developing mental health problems (11)(12)(13). On the other hand, it is known that excessively long working hours may lead to short sleep and fatigue due to insufficient recovery between work shifts (14)(15)(16)(17)(18)(19), which have been associated with an increased risk of developing mental health problems (20)(21)(22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%